Pemanfaatan ekstrak daun kelor (Moringa oleifera L.) dalam minyak zaitun (Olea europea L.) sebagai obat penyembuh luka bakar - Monica, Agata Bella (Maliki Interdisciplinary Journal, 2024)
Indonesia is a tropical country that has a variety of biodiversity, one of which is the Moringa plant. Moringa is a herbaceous plant that is easy to grow in various regions of Indonesia. One part of the Moringa plant that can be used is the leaves. Moringa leaves contain secondary metabolites. Secondary metabolite compunds contained in Moringa leaves are phenolic compounds, flavonoids, tannins, carotenoids, steroids, and tannins where these compunds can be effectively used as a source of antioxidants, anti-inflammatories, and antibacterials. This study aims to determine the benefits of Moringa leaf extract in olive oil extract which can heal burns. The method used is through a theoretical approach. The results obtained show that Moringa leaf extract in olive oil can heal burns by applying it regularly to the wound without being accompanied by the use of drugs from a doctor.